ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT PTOFESIONAL TELEKOMUNIKASI INDONESIA (PRTL) - Riyan Rama Putra; Triana Lidona Aprilani; Baiq Dewi Lita Andiana; Dara Nida Utamie (Yayasan Nusantara Hasana Berdikari, 2025)
PT Profesional Telekomunikasi Indonesia Tbk (PRTL) officially took over 94.03% of PT Solusi Tunas Pratama Tbk (SUPR) shares. Acquisition is the takeover of ownership or control of shares or assets of another company, either partially or in whole, where both companies continue to exist as separate legal entities. This study was conducted to determine the differences in financial performance before and after the acquisition of PT Profesional Telekomunikasi Indonesia for the period 2018 - 2023. This research method uses quantitative with comparative analysis, using data analysis techniques through the Excel Application and graphical analysis based on PT Protelindo's annual financial report. The results of the analysis showed a significant decrease in the liquidity and solvency ratios post-acquisition, although several profitability and activity ratios showed an increase. Overall, PRTL's financial performance tended to deteriorate after the acquisition, indicating challenges in maintaining short- and long-term financial stability. This study concludes that acquisitions do not always guarantee improved financial performance and emphasizes the importance of careful planning and integration post-acquisition. These findings provide theoretical and practical implic